THE THEORY OF CIVILIZATIONS THROUGH THE LENS OF CONTEMPORARY HUMANITIES - T. V. Danylova (Antropologìčnì Vimìri Fìlosofsʹkih Doslìdžen')
Purpose. This paper invites reflections on the further development of civilizational theory through the lens of contemporary humanities. It argues that philosophy is one of the key dimensions of the integral theory of civilizations. The purpose is to promote dialogue-rich interdisciplinary civilizational approach with philosophical understanding of human essence at its core. Methodology. The author has used comparative historical analysis, along with hermeneutical methodology and interdisciplinary approach. Theoretical basis and results. Faced with the challenges of our time, researchers are turning to the civilizational approach, according to which world history appears to us as a colourful spectrum of the options for the development of humanity. At the present stage of scientific development the integral theory of civilizations seems to be the most productive tool for the interpretation of the events taking place in our world. Origianlity. The problem of human being is a key factor in understanding the dynamics of civilizational process and designing a promising theory of civilizations. Philosophy should occupy an important place in the development of a new theory of civilizations: philosophy is the spiritual quintessence of every epoch, every cultural and civilizational community. In particular, a new theory has to take into account both classic and contemporary investigations in the field of philosophical anthropology and theory of values. The increasing threat posed by the clash of civilizations can become a swan song of humanity. For the preservation and further development of the world civilization, there is no other choice but to elaborate the strategies, mechanisms for consultation and dialogue, cooperation and partnership of civilizations and states. That is why the urgent task is to create the certain philosophical position that will contribute to mutual understanding. Conclusions. It is important to involve philosophers in the development of a new integral theory of civilizations. We need to unite our efforts for the sake of human survival. It is only by a constructive and respectful dialogue that humanity will truly overcome mutual misunderstanding, controversy, and aggressiveness. As a result of it, people will realize that the world is much smaller than they previously imagined, and to preserve it the absolute value in the diversity of world civilizations has to be recognized.